Information politics: strategies and counterstrategies. (1st January 2014) - Grover, Varun; Sabherwal, Rajiv; Raman, Roopa; Gokhale, Rahul A.
Despite the increasing importance and pervasiveness of information systems, many of them fail to gain traction. We contend that information politics is a major cause of these failures and must be counteracted and managed. We focus on uncovering and delineating the covert political strategies that are often employed against information systems projects and the counterstrategies that are found to be most effective against them. We collect narrative descriptions of politics encountered in 141 information systems projects. Through an iterative analysis of the data, we profile five types of political behaviours: pretending, toddling, hostage taking, stickling, and masterminding, based on how the players choose to exhibit resistance. Political manoeuvring through each behaviour is illustrated. We then describe counterstrategies through which different political behaviours can be managed during the project as well as planned for ex ante. The article serves as a reality check for appreciating the role of information politics and applying pragmatic but simple ways in which IS projects could be kept on course.